SPATIAL AND TEMPORAL DISTRIBUTION OF PSEUDOMONAS AERUGINOSA SPECIE IN SURFACE LAGOON WATER - Ebohon, Joy Osiuare; Agwu, O. A.; Oluwagunke, T. O.; Bello, I. A.; Lampejo, A. M.; Mohammed, H. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Pseudomonas aeruginosa is a ubiquitous bacterium in diverse environment, and has been implicated in various ecological and clinical activities. The present study assessed the spatial and temporal prevalence of P. aeruginosa in Lagos Lagoon surface water by isolation and enumeration of the culturable bacteria on two selective media (Cetrimide and Acetamide agar) and species identification was done by applying different biochemical test. Enumeration of the P. aeruginosa isolate observed throughout this study in the twelve stations sampled ranged from 2.5 – 57000.0 CFU/100ml. The percentage population density was highest (54.75%) at the peak of rainy season (July) while the other sampling period had less than 20%. The two stations (5 and 7) with 25.33% and 24.82% population density are notable for high anthropogenic activities. The counts of P. aeruginosa were not correlated with any of the physico-chemical parameters tested. The temporal and spatial percentage population density indicate possible higher contamination during rainy season due to increased runoff and that higher human activity obviously contributes to contamination respectively. This highlights potential consequence to human health and seafood safety as well as the possible ecological roles particularly in the breakdown of pollutants and other biotechnological benefits.
Keywords: Pseudomonas aeruginosa; Lagoon; surface water; pollution